DANA DESA DAN PERUBAHAN SOSIAL DI DESA (STUDI KASUS DESA PERBANGUNAN KECAMATAN SEI KEPAYANG, KABUPATEN ASAHAN) - Sitohang, Halomoan (CV. Lafadz Jaya, 2024)
The aim of this research is to find out and analyze the use of village funds in the development village of Sei Kepayang District using the theory of structural functionalism from Robert K. Merton. This research uses qualitative research methods. This method was chosen in order to obtain in-depth and comprehensive research data regarding the lives of farmers in the Development Village of Sei Kepayang District after the village funds were rolled out, which later the data obtained will then be presented using Robert K. Merton's structural functionalism theory. From the results of this research, it was found that (1) Changes in Development Villages with the decline in village funds were increasingly marked by an increase in the welfare of farmers. The circulation of village funds is certainly functional for farmers in general, marked by improvements in facilities and infrastructure in the agricultural sector because development carried out with village funds means the introduction of modern agricultural equipment because road infrastructure is improved, this of course reduces production costs or makes it easier for farmers to cultivate his agricultural land. Water availability is sufficient throughout the year (2) in R.K. Merton Social Theory and Social Structure divides functions into two, namely manifest (intended) functions and latent (unintended) functions. Manifest functions are functions that are expected in society, while latent functions are functions that are not expected. So, regarding the Village Fund, its manifest function is increasing the welfare of the people in the Village, while one of its latent functions is starting to fade the marsiruppa pattern. (3) Meanwhile the dysfunction is the loss of job opportunities for some people who work as agricultural laborers (4) for non-function is Farming communities continue to uphold local wisdom.